Expansion of Granulocytic, Myeloid-Derived Suppressor Cells in Response to Ethanol-Induced Acute Liver Damage - Li, Sha; Wang, Ning; Tan, Hor-Yue; Hong, Ming; Yuen, Man-Fung; Li, Huabin; Feng, Yibin (Frontiers in Immunology, 2018)
The dual role of ethanol in regulating both pro-inflammatory and anti-inflammatory response has recently been reported. Myeloid-derived suppressor cells (MDSCs) are one of the major components in the immune suppressive network in both innate and adaptive immune responses. In this study, we aim to define the role of a population expressing CD11b+Ly6GhighLy6Cint with immunosuppressive function in response to ethanol-induced acute liver damage. We find this increased granulocytic-MDSCs population in the blood, spleen, and liver of mice treated with ethanol. Depletion of these cells increases serum alanine aminotransferase and aspartate aminotransferase levels, while granulocytic-MDSCs population adoptive transfer can ameliorate liver damage induced by ethanol, indicating the protective role in the early stage of alcoholic liver disease. The significant changes of T-cell profiles after granulocytic-MDSCs populations adoptive transfer and anti-Gr1 injection signify that both cytotoxic T and T helper cells might be the targeted cells of granulocytic-MDSCs. In the in vitro study, we find that myeloid precursors preferentially generate granulocytic-MDSCs and improve their suppressive capacity via chemokine interaction and YAP signaling when exposed to ethanol. Furthermore, IL-6 serves as an important indirect factor in mediating the expansion of granulocytic-MDSCs populations after acute ethanol exposure. Collectively, we show that expansion of granulocytic-MDSCs in response to ethanol consumption plays a protective role in acute alcoholic liver damage. Our study provides novel evidence of the immune response to acute ethanol consumption.